(untitled) (Research, Society and Development, 2020)
This study aimed to evaluate the effects of potassium fertilization on Myracrodruon urundeuva, Libidibia ferrea and Mimosa tenuiflora seedlings submitted to a short period of water deficit. Three doses of K (0, 150 and 300 mg dm-3 KCl) and three water regimes (without water deficit, moderate water deficit and severe water deficit) were evaluated. The plants were kept in black plastic bags containing soil from the Caatinga and, 30 days after the beginning of the water regimes, the relative water content (RWC), transpiration (E), stomatal conductance (gs) and photosynthesis (A) were evaluated. High moisture content in the soil was unfavorable to plants, promoting reduction in RWC and gas exchange. The water deficit increase E, gs and A, but the intensity of these responses was variable between species. The water deficit favored L. ferrea, with elevated RWC and reduced alterations in gas exchange, demonstrating its greater tolerance in relation to the others species evaluated, however it was the species most benefited by K. The supply of 300 mg dm-3 of KCl positively influenced the water status and gas exchange of the studied species with an increase in the water deficit. We suggest the development of research subjecting the plants to a longer period of time, in order to establish a better relationship between potassium and the increased tolerance of these plants to water deficit.